ADIPONEKTIN HIGH MOLECULAR WEIGHT DAN KEKAKUAN VASKULAR DI PENYAKIT DIABETES MELITUS TIPE 2 TERKAIT GABUNGAN GLIMEPIRIDE METFORMIN DOSIS TETAP - Sutjahjo, Ari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Diabetic patients have the tendency to develop micro vascular and macro vascular complications due to the hyperglycaemic state. Thereare various types of oral hypoglycaemic agents available in Indonesia, nevertheless, these agents fail to decrease mortality and morbiditydue to the endothelial dysfunction in diabetic patients. It is not yet known whether glimepiride metformin fixed dose combination isable to improve the serum High Molecular Weight (HMW) adiponectin and vascular stiffness which are important parameters of thecardiovascular risk factors. This study was to know the effect of glimepiride metformin fixed dose combination by investigation after 12weeks of treatment towards HMW adiponectin level and vascular stiffness using ba-PWV in type 2 diabetes. This research was carried outby a Quasi experimental study with pre and post test design. The subjects were type 2 diabetes patients who came to the EndocrinologyOutpatient Clinic at the Dr. Soetomo Hospital and 6 health centres in Surabaya during December 2010 to December 2011. In this study,measuring the HMW adiponectin level in plasma was by using ELISA method and the ba-PWV by using the V Serra-1000 before and aftertreatment with glimepiride metformin fixed dose for 12 weeks. Based on the thirty five type 2 diabetic patients who met the inclusion andexclusion criteria and who were enrolled in this study, after 12 weeks of treatment, the median HMW Adiponectin level was increasedfrom 1736 ng/mL to 1770 ng/mL, which was statistically not significant (p=0.317). After 12 weeks treatment, the median of ba-PWVwas decreased from 1580 cm/sec to 1450 cm/sec, which was statistically significant (p=0.028). The level of HMW adiponectin was notsignifantly different between before and after treatment. The level of brachial ankle Pulse Wave Velocety (ba-PWV) was significantlydifferent between before and after treatment. Glimepiride metformin fixed dose combination decreases the vascular stiffness, which isone of the parameters of the endothelial dysfunction.